THE TERRITORIES OF THINKING AND FEELING: RETHINKING RELIGION, SCIENCE, AND REASON WITH ALISTER McGRATH: with Bethany Sollereder, "Introduction to Essays in Honor of Alister McGrath"; Peter Harrison, "What is Natural Theology? (And Should We Dispense with It?)"; John Hedley Brooke, "Revisiting William Paley"; Helen De Cruz, "A Taste for the Infinite: What Philosophy of Biology Can Tell Us about Religious Belief"; Michael Ruse, "The Dawkins Challenge"; Donovan O. Schaefer, "The Territories of Thinking and Feeling: Rethinking Religion, Science, and Reason with Alister McGrath"; Andrew Pinsent, "Alister McGrath and Education in Science and Religion"; Andrew Davison, "Science and Specificity: Interdisciplinary Teaching between Theology, Religion, and the Natural Sciences"; Victoria Lorrimar, "Does an Inkling Belong in Science and Religion? Human Consciousness, Epistemology, and the Imagination"; and Alister E. McGrath, "Response: Science and Religion—The State of the Art." (Zygon: Journal of Religion & Science, 2022)
As Alister McGrath has argued across a lifetime of work, we need to approach the binaries that have been handed down to us—personal/academic, emotional/intellectual, secular/religious—with a healthy skepticism toward the integrity of their boundaries, attending instead to the contact zones between them. This article connects McGrath's body of work to what I call "cogency theory," an approach that rejects the thinking/feeling binary itself. It begins with a survey of how McGrath understands rationality—not only as multiple, but as defined, in meaningful ways, by feeling. This is illustrated by reexamining McGrath's controversy with Richard Dawkins, analyzing their debate in terms of how the argument itself comes to feel. This new paradigm allows us to supersede petty antagonisms built into contemporary culture—like the presumed science–religion conflict—and refocus on overarching concerns like the climate crisis. The article concludes with a question about the extent to which beliefs and "worldviews" define how we—either as groups or individuals—can make or unmake ecological disaster.